Multiple Positive Solutions of Second-Order Nonlinear Difference Systems with Repulsive Singularities - Shengjun Li; Fang Zhang (Journal of Function Spaces)
We study the existence of positive solutions for second-order nonlinear repulsive singular difference systems with periodic boundary conditions. Our nonlinearity may be singular in its dependent variable. The proof of the main result relies on a fixed point theorem in cones and a nonlinear alternative principle of Leray-Schauder; the result is applicable to the case of a weak singularity as well as the case of a strong singularity. An example is given; some recent results in the literature are improved and generalized.